Isolation and characterization of starch from defatted rice bran - Fabian, Cynthia B. (Animo Repository, 2011)
Rice starch is one of the most expensive yet very useful starches due to its unique characteristics. This study aimed to isolate starch from defatted rice bran, an underutilized byproduct of milling and is a relatively inexpensive source of rice starch. Starch was extracted from the bran by first soaking it in water. The mixture was then subjected to blending and washing with water, alcohol and alkali solution. About 83% of the rice bran starch was recovered. Characterization of the rice bran starch showed that its gelatinization and retrogradation properties as well as its granule size are similar to those of starch from rice endosperm. Based on the results of this study, defatted rice bran can be a good source of starch that is suitable for applications in food and pharmaceutical industry and other new applications such as a potential material in the biomedical field.